2022
DOI: 10.1186/s43166-022-00160-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse in granulomatosis with polyangiitis: a multi-center study

Abstract: Background Granulomatosis with polyangiitis (GPA) is a rare systemic vasculitis. Its severity ranges from indolent disease to fulminant that may cause death. With treatment, remission is seen in more than 80% of cases, although relapse is still common. There have been studies showing that there may be factors to predict relapse in GPA. Based on relapses, the decision to start treatment and/or to monitor the patients more closely is made. Therefore, predicting the relapse of GPA can be effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 44 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…As a result, many patients are maintained on long‐term immunosuppression, sometimes indefinitely, to avoid relapse. Studies examining predictors of relapse in AAV reported a higher relapse risk among patients with anti‐proteinase 3 (PR3)‐ANCA type (vs anti‐myeloperoxidase‐ANCA) as well as prior ENT, gastrointestinal, or lung involvement 3,21 . Our study builds upon these findings by identifying a high‐risk subgroup among patients already with higher risk features (eg, GPA, mostly PR3‐ANCA positive, with a history of sinonasal disease).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…As a result, many patients are maintained on long‐term immunosuppression, sometimes indefinitely, to avoid relapse. Studies examining predictors of relapse in AAV reported a higher relapse risk among patients with anti‐proteinase 3 (PR3)‐ANCA type (vs anti‐myeloperoxidase‐ANCA) as well as prior ENT, gastrointestinal, or lung involvement 3,21 . Our study builds upon these findings by identifying a high‐risk subgroup among patients already with higher risk features (eg, GPA, mostly PR3‐ANCA positive, with a history of sinonasal disease).…”
Section: Discussionmentioning
confidence: 73%
“…Studies examining predictors of relapse in AAV reported a higher relapse risk among patients with anti-proteinase 3 (PR3)-ANCA type (vs anti-myeloperoxidase-ANCA) as well as prior ENT, gastrointestinal, or lung involvement. 3,21 Our study builds upon these findings by identifying a high-risk subgroup among patients already with higher risk features (eg, GPA, mostly PR3-ANCA positive, with a history of sinonasal disease). Further work is needed to determine the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations